Nursing care of a 69-year-old patient after a stroke staying in the neurological ward - Bogusława Ryś; Aneta Gruszczyk (Kazimierz Wielki University, 2024)
The presented work focuses on the description of issues related to ischemic stroke and the presentation of the patient's care process after this incident. The first part is a clinical description of the disease, and the second part is a case report of a patient after an ischemic stroke staying in a neurological ward. The work also includes a description of the course of hospitalization, nursing problems, nursing interventions undertaken and evaluations of nursing activities.